Identification of immunogenic KIF5B-RET fusion neopeptides driving immune stimulation in tumor specific CD8+ T cells - Castillo, Micah B.; Rankothgedera, Sakuni; Thevasagayampillai, Shiyanth; Kandasamy, Aaranyah; Lewis, Jaila; Woody, Cole; Vaz de Freitas, Martiela; Antunes, Dinler Amaral; El-Zein, Randa; Gunaratne, Preethi H. (Frontiers in Immunology, 2025)
IntroductionNon-classical neoantigens at the fusion junctions of chimeric RNAs are tumor- specific with a low risk of autoimmunity and therefore represent ideal targets for personalized vaccines. We present a platform to discover immunogenic neoantigens that drive CD8+ T cell clonotypes from chimeric RNA fusion junctions to promote tumor-reactive T cell expansion and prevent tumor recurrence following immunotherapies.MethodsRNA sequencing data from 15 Lung Adenocarcinoma and 15 Squamous Cell Carcinoma patients (tumor and adjacent normal tissues) were analyzed. The KIF5B [Exon 1-15] | RET [Exon 12- 19] fusion was selected from a patient-derived xenograft (PDX) model based on its established role as an actionable cancer driver in an independent tumor with the same junction. We assessed the affinity of neopeptides from the KIF5B-RET fusion to MHC Class I molecules using in silico tools MHCNuggets and MixMHCPred 2.ResultsHLA-C07:02 showed the highest affinity for 9-mer peptideswith NNDVKEDPK, which emerged as the strongest binder based on HLA-Arena docking and binding energy calculations. Immunogenicity was evaluated by IFNg Enzyme-Linked Immunosorbent Spot (ELISpot) assays using HLA-C07:02- matched Peripheral Blood Mononuclear Cells (PBMCs) from two donors. CD8+ T cells from both donors responded to specific junction peptides. Single-cell 5’gene expression RNA sequencing and T Cell receptor mapping of activated T cells identified 15 TCR clonotypes, five of which had high activation. Key residues in CDR3a and CDR3b are crucial for CD8+ T cell activation. NNDVKEDPK and KEDPKWEFP showed minimal cross-reactivity with the normal tissues.DiscussionThis study demonstrates a robust pipeline for identifying and validating immunogenic neoantigens from chimeric RNAs to design personalized cancer vaccines with high immunogenicity and low cross-reactivity.